Robotics technologies for 3D printing - Hartato, Gilbert Alexander (2019)
3D Printing, which is a sub branch of Additive Manufacturing (AM) has been popular the manufacturing alternatives for decades. It has advantages over the traditional manufacturing processes, especially when an object with complex geometry needs to be created. Although it has been widely used, current conventional 3D printers are only limited to 3 axes of motion, X, Y and Z axis. Because of this limitation, they can only print on a flat surface. Therefore, the aim of this project is to investigate on the application of robotic technologies to enable 3D printing with greater than 3 Degrees-of-Freedom i.e spatial position and orientation. This report will cover the application inverse velocity kinematics on a 4 Degree-of-Freedom robotic arm.